Digital Innovation and Rapid Application Development: A New Approach to Staff and Lecturer Recruitment at University - Enzelin, Lola Naomi; Oetama, Raymond Sunardi; Anggina, Rhauma Syira (Journal of Information System and Informatics, 2024)
The University encountered challenges with its manual recruitment processes, characterized by inefficient record-keeping, decreased productivity, and prolonged hiring periods. To address these issues, a recruitment application was developed using the Rapid Application Development (RAD) methodology, prioritizing swift iterations and comprehensive stakeholder involvement. We have implemented many features to improve the user experience for job seekers and employers. It includes sign-up and login options for both, CV uploading for job seekers, and the ability to view vacancies. Employers can also view and upload vacancies, delete them if needed, and schedule interviews through the system. Both job seekers and employers can easily edit their profiles and passwords, ensuring flexibility and usability throughout the recruitment process. Notably, User Acceptance Tests revealed high satisfaction levels among users, confirming the application's effectiveness in meeting their requirements and enhancing the overall recruitment experience. The application's user-centric design and agile development approach represent a substantial advancement in the University's recruitment practices.